(untitled) (Fiep Bulletin - online, 2014)
The aim of this study was to verify the effectiveness of the endovaginal electrical stimulation associated with the specific kinesiotherapy for the pelvic floor in menopausal women who presented stress urinary incontinence. The sample was composed of 15 women, at the median age of 61,3 years, who presented urinary loss due to small, average and great efforts. After applying the techniques, the results demonstrated the effectiveness of the conservative treatment, which was noticed by the improvement of the condition through quantifiable parameters, like the test of Anus Elevators Strength that had a significant improvement from 3,2 to 4.7 on average (p = 0,05). The average of use of daily protections also presented a significant reduction from 1,9 to 0,2 (p = 0,05), as well as the episodes of leakage in daily activities like sneezing, coughing, laughing and lifting weight.